Time trends and determinants of the method of payment in M&As - Boone, Audra L.; Lie, Erik; Liu, Yixin (Journal of Corporate Finance, 2014)
We examine the time trends and determinants of the method of payment in M&As spanning four decades. The fraction of mixed payments tripled from about 10% before the turn of the century to 30% in the new century, while the fraction of stock (cash) payments peaked (bottomed out) in the late 1990s but has since plunged (surged). We can explain a portion, but not all, of these trends using explanatory variables linked to adverse selection theory, taxation, and contracting costs. We also show that mixed payments are not merely hybrids between cash and stock payments, but have unique determinants and features.